EFEKTIFITAS PEMBERIAN POSISI MIRING KIRI DAN SETENGAH DUDUK TERHADAP KEMAJUAN PERSALINAN KALA SATU FASE AKTIF DILATASI MAKSIMAL PADA PRIMIGRAVIDA - Lestari, Yusri Dwi; Hasanah, Suhul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Care for the mother dear has a strategic role to reduce stress and anxiety during labor. One of the implementations of the maternal love program is to recommend several positions during labor and delivery of the baby. This study was intended to determine the relationship between giving a sitting and half-sitting position to the progress of labor when the active phase is maximal dilated. The purpose of this study was to find out the effectiveness of giving a left and half sitting oblique position. The type of research used is correlational analytic research. Statistical analysis using Mann Withney. The results showed that the effectiveness of the left oblique position was more than 2 hours 1 respondent or 25%, while the progress of labor for 2 hours 3 respondents or 75%, while being positioned half sitting, getting progress of labor more than 2 hours 25%, while progress delivery for 2 hours is 75%. From the results of the study it was found that there was no difference between giving the left and half sitting oblique position. So that these two positions can be used to accelerate the progress of labor.Keywords: position, progress of labor